A Preliminary Study Investigating Industrial Designer Role In Malaysian Furniture Industry - Mohammad, Suhirman; Rahman, A. Rizal; Dolah, Sharizal (2016)
The study has been conducted to investigate the Industrial Designer role in Malaysian Furniture Industry to understand challenges faced by the industrial Designer and to explore the current situations involved with Industrial Designer in furniture Industry. The study wills involve interviews and observations data collection work with Industrial Designers and Furniture Manufacturing companies in the current environment. As this research is still an ongoing investigation, we found that in Malaysia the role of industrial designers in furniture industry has not specified and Industrial Designers are required to perform many different tasks which has not been taught in their studio learning experience. This research work hope to find some career path system involved with Industrial Designer in furniture Industry or as a specific guidelines to establish the role of designer especially in Malaysia Furniture manufacturing industries, which can be beneficial to the industry as well as design education in Malaysia